Discovery of structural diverse reversible BTK inhibitors utilized to develop a novel in vivo CD69 and CD86 PK/PD mouse model. (15th January 2023) - Vandeveer, George H.; Arduini, Robert M.; Baker, Darren P.; Barry, Kevin; Bohnert, Tonika; Bowden-Verhoek, Jon K.; Conlon, Patrick; Cullen, Patrick F.; Guan, Bing; Jenkins, Tracy J.; Liao, Shu-Yu; Lin, Lin; et al.
Graphical abstract: Abstract: For the past two decades, BTK a tyrosine kinase and member of the Tec family has been a drug target of significant interest due to its potential to selectively treat various B cell-mediated diseases such as CLL, MCL, RA, and MS. Owning to the challenges encountered in identifying drug candidates exhibiting the potency block B cell activation via BTK inhibition, the pharmaceutical industry has relied on the use of covalent/irreversible inhibitors to address this unmet medical need. Herein, we describe a medicinal chemistry campaign to identify structurally diverse reversible BTK inhibitors originating from HITS identified using a fragment base screen. The leads were optimized to improve the potency and in vivo ADME properties resulting in a structurally distinct chemical series used to develop and validate a novel in vivo CD69 and CD86 PD assay in rodents.